2018
DOI: 10.22207/jpam.12.4.52
|View full text |Cite
|
Sign up to set email alerts
|

Methane from Human Excreta: Comparative Assessment of Batch and Continuous Biomethanation Process

Abstract: Treatment of human excreta (HE) is necessary before its discharge into natural water body. Untreated discharge may cause several ill effects for environment and human health. Anaerobic digestion of human excreta can unravel this problem along with production of biogas. Anaerobic digestion process may be either batch type or continuous type. In present study, human excreta were degraded anaerobically by both the means in the laboratory scale 5L capacity glass digesters. The comparative assessment between batch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The biodegradability rate achieved in the present study is consistent with the COD removal percentages reported in previous studies based on SWS BMP assays, such as Maragkaki et al (2018) , Kashi et al (2017) , and Zhang, Hu & Lee (2016) , which achieved removal percentages of 28.9%, 16.0%, and 25.2%, respectively. OM is measured by the amount of carbon in a feedstock ( Ferguson, Coulon & Villa, 2018 ; Gohil et al, 2018 ) and biomethane yield is affected by the VS content ( Mayer et al, 2014 ). Therefore, CH 4 production is directly related to the degradation of VS ( Angelidaki et al, 2009 ) being VS the OM component of TS.…”
Section: Discussionmentioning
confidence: 99%
“…The biodegradability rate achieved in the present study is consistent with the COD removal percentages reported in previous studies based on SWS BMP assays, such as Maragkaki et al (2018) , Kashi et al (2017) , and Zhang, Hu & Lee (2016) , which achieved removal percentages of 28.9%, 16.0%, and 25.2%, respectively. OM is measured by the amount of carbon in a feedstock ( Ferguson, Coulon & Villa, 2018 ; Gohil et al, 2018 ) and biomethane yield is affected by the VS content ( Mayer et al, 2014 ). Therefore, CH 4 production is directly related to the degradation of VS ( Angelidaki et al, 2009 ) being VS the OM component of TS.…”
Section: Discussionmentioning
confidence: 99%